Design and development of A 4-dof SCARA robot for educational purposes - Mohamed Sahari K.S.; Weng K.H.; Han Y.W.; Anuar A.; Baharuddin M.Z.; Mohideen S.S.K. (Penerbit UTM Press, 2023)
Robotics have become a common course in a lot of higher institutions. Although there are many robots available in the market, most of them are for industrial purposes and are costly. There is a need to develop low cost robots for students in higher institutions to learn the elements of robotics such as design, kinematics, dynamics, sensing and control. The aim of this project is to design and develop a mechanical structure of a SCARA robot that can perform certain tasks for educational, research and exhibition purposes such as pick and place operation. The paper discusses the steps used in design and development of a 4 degree of freedom (DOF) SCARA robot which includes specification definition, conceptual design, product development, and testing. In specification definition phase, the specifications of the SCARA robot are first determined. After that, the best conceptual design of the SCARA robot is chosen after making concept evaluation in the conceptual design phase. Then, in third phase which is the product generation, the chosen design of the SCARA robot is fine-tuned. Stress analysis using finite element analysis is carried out before a prototype is developed. The direct and inverse kinematics, dynamics of the robot are then modeled. Off shelf parts are also selected based on the derived parameters from calculations. Electronic parts such as sensors and dedicated controller using low cost microcontroller are then developed. Finally, the developed SCARA robot is tested to see whether it fits the targeted specifications. Universiti Teknologi Malaysia.